Smart embedded PZT sensor for in-situ elastic property and vibration measurements in concrete. (March 2021) - Kocherla, Amarteja; Duddi, Murali; Subramaniam, Kolluru V.L.
Highlights: Embeddable PZT sensor for vibration monitoring of concrete structure is developed. Structural vibration monitoring capability of the sensor is validated. The embedded sensors detect the transient vibratory motion of the concrete structures immediately after setting. Elastic property development of hydrating concrete determined using embedded sensors in a standard vibration setup. Abstract: An embeddable PZT-based sensor, which is capable of detecting transient dynamic motion for vibration measurement from a concrete structure, is presented. A circular PZT patch, which provides uniform in-plane sensing capability, is used to develop the sensor. The validity of vibration measurements obtained from the embedded PZT sensor is established using a standard setup. The influence of the orientation of the PZT sensor on capturing the different vibrational modes of the concrete cylinder is studied. The transient dynamic signatures captured from the embedded sensors in a vibration measurement match those obtained from surface mounted accelerometers. The elastic properties of hydrating concrete are determined from the vibration measurements of standard cylinders obtained using the embedded PZT sensors. The ability of the embedded sensors to detect low-level, transient vibration of the concrete structures immediately after setting is demonstrated. The vibration measurements provide a continuous measure of increasing stiffness of an aging concrete medium.